A Study of the Competencies in Managing Business Continuity of Thai Traditional Construction Firm Owners - Wongmahadlek, Panita (Humanities, Arts and Social Sciences Studies, 2020)
Throughout time, traditional Thai architecture has persisted as one of the most important reflections of “Thainess” upon Thai culture. The traditional construction method has been handed down from generation to generation through the traditional process called “master-apprentice relationships” for centuries. However, the traditional skill training system have been replaced from the individual scale to vocational schools with modern construction techniques entailed. The number of traditional craftsmen and knowledge has slowly diminished. One of the important factors in preserving such heritage is the survival of construction companies where masters and their apprentices are retained. The discontinuity of these traditional construction companies is not only harmful to their business but also jeopardize on the national asset in a way. The highlight of this study is on entrepreneurs as the key people to set a company’s direction so as to create an ability to withstand business disruption and crisis. This study aimed to investigate the competency of construction firm entrepreneurs whose main practice is based on Thai traditional construction knowledge in order to determine the readiness of such firms to survive over the business disruption and sustain their knowledge capital of traditional construction methods. The findings indicate that entrepreneurial commitment as well as passion and social skills are distinctive and crucial for sustaining success. Next, the knowledge and skill in Thai tradition construction are inevitable. However, the entrepreneurs mostly place priority on technical knowledge and skills while organizational skills are rather overlooked. It is the missing ability to see an organization as a whole with a systematic viewpoint. Moreover, both of the generation gap and lack of interest in Thai traditional construction were found to be a hindrance in ownership succession. The next generation with different attitude is one of the main reasons directed to business disruption.